Human resource champions : the next agenda for adding value and delivering results - Ulrich, David, 1953- (Boston : Harvard Business School Press, 1997)
For companies striving to meet the competitive challenges of today and tomorrow - including globalization, technology, profitability through growth, and capacity for change - the management of human resources holds the key to future success. Ulrich urges a shift of the HR professional's mentality from "what I do" to "what I deliver" and identifies four distinct roles that human resources staff must assume in order to make the transition: strategic partner, administrative.
expert, employee champion, and change agent. Full of examples from dozens of companies that have transformed their HR functions, Human Resource Champions provides hands-on tools that show HR professionals how they can operate in all four areas simultaneously. It offers specific recommendations for HR staff and line managers about how to establish a partnership to deliver value and make their organizations more competitive.
1. The Next Agenda for Competitiveness: Human Resources -- 2. The Changing Nature of Human Resources: A Model for Multiple Roles -- 3. Becoming a Strategic Partner -- 4. Becoming an Administrative Expert -- 5. Becoming an Employee Champion -- 6. Becoming a Change Agent -- 7. HR for HR -- 8. What's Next?
Includes bibliographical references (p. 255-271) and index.
Keywords: Personnel management; Organizational change; Personeelsmanagement; Organisatieverandering; Personnel -- Direction